Non Local Effects in the Sznajd Model: Stochastic resonance aspects - Gimenez, Maria Cecilia (2012)
The Sznajd model is basically an Ising spin model, widely used in sociophysics studies as a simple mechanismfor predicting decision-making in a closed community through interactions among the nearest neighbors.In the present work we aim to deepen our understanding of this model by analyzing not only local or firstneighbor interactions but also long range ones. Besides, we consider the system as being subjected to twosignals, a stochastically social internal one, mimicking “social temperature”, and an external periodic signalplaying the role of the effects of fashion or propaganda. Under these conditions, we show the occurrence of adouble stochastic resonance phenomenon when depicting signal-to-noise ratio as a function of both, the socialtemperature and the non local interaction parameters.